Brenda Milner: Pioneer of the Study of the Human Frontal Lobes - Kolb, Bryan (Frontiers in Human Neuroscience, 2022)
Although the behavioral effects of damage to the frontal lobes date back to at least the late 19th century even midway through the 20th century very little was known about human frontal lobe function and there was a general consensus that the frontal lobe did not play a key role in cognition. This all changed when Brenda Milner published a chapter in a 1964 volume entitled: The Frontal Granular Cortex and Behavior. Milner’s chapter, “Some effects of frontal lobectomy in man,” was the first systematic study of the effect of frontal lobe excisions on cognition in human patients. Milner had access to a unique population of frontal excision patients at the Montreal Neurological Institute that were being treated by Wilder Penfield and his associates for a wide range of neurological disorders, including intractable epilepsy. Milner and her colleagues engaged in a more than 50-year study that has had a formidable impact on our understanding of frontal lobe function. Paralleling studies of frontal lobe function in non-humans they influence on understanding the evolution and function of the prefrontal cortex of mammals. Thus, although Brenda Milner is best known for her studies of human memory, she has had an equally important contribution to our understanding of the frontal lobes.